2018
DOI: 10.1101/490904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of biological sex on alternative splicing

Abstract: Over 95% of human genes undergo alternative splicing (AS) in a developmental, tissue-specific, or signal transduction-dependent manner. A number of factors including binding of cis-acting sequences by RNA-binding proteins (RBPs) are known to affect AS, but the combinatorial mechanisms leading to the distribution of spliced isoforms remain largely unstudied. Here, in 9011 samples from 532 individuals across 53 tissues from the Genotype-Tissue Expression (GTEx) resource, we identified 4,135 genes with sex-biased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Several previous studies observed the same association in MDS and AML; however, it did not reach statistical significance in some cases because of small sample numbers. 25,26 Furthermore, it was suggested that sex has an impact on splicing profiles of various tissues, and the degree of global aberrant splicing was reported to be higher in men with MDS compared with women with the same disorder. 8,9 Future studies that are better designed to examine sex-specific genetic backgrounds and clinical associations with SF mutations, including treatment outcome, should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies observed the same association in MDS and AML; however, it did not reach statistical significance in some cases because of small sample numbers. 25,26 Furthermore, it was suggested that sex has an impact on splicing profiles of various tissues, and the degree of global aberrant splicing was reported to be higher in men with MDS compared with women with the same disorder. 8,9 Future studies that are better designed to examine sex-specific genetic backgrounds and clinical associations with SF mutations, including treatment outcome, should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…FDXR-206 was the most responsive to IR in men. Sex differences in gene expression have been widely reported [33], and differences in gene variants distribution between genders have also been identified in humans [34,35] and mice [36]. Even though the gender groups were relatively small (n = 5) in the present study, gender bias was examined in eight variants, but no significant differences were identified apart from FDXR-206 at the single highest dose of 4 Gy.…”
Section: Discussionmentioning
confidence: 54%
“…Although 12% of the 65 genes overlapping the 162 DMPs showed sex-specific placental expression, the majority were not significantly differentially expressed by placental sex. This is may be related to the small sample size of the gene expression cohort utilized (n=34), the role of additional factors beyond DNAme in regulating gene expression, and the possibility of alternative splicing and sex-specific isoform expression, which would not be captured in microarray analysis (66). Additionally, sex differences in DNAme at these 162 DMPs may be involved in regulating the expression of genes beyond those they overlap, which would not have been captured in this candidate gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%